FINANCIAL LITERACY EDUCATION AMONG ASNAF STUDENTS IN SECONDARY SCHOOLS: EVIDENCE FROM PERLIS - Muhammad Ahmar Ali; Shafawaty Mohamad Shabri; Siti Nor Junita Mohd Radzi; Ahmad Zulhusny Rozali (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
It is especially important for young Asnaf students to acquire the financial knowledge necessary for them to make informed decisions that can positively impact their life trajectories. This study investigated the level of financial literacy among Asnaf students in secondary schools across Perlis. Financial literacy is assessed through three core dimensions: financial knowledge, financial behaviour, and financial attitudes. A total of 400 respondents were selected from various secondary schools in Perlis. Data were collected using questionnaires, and descriptive analyses were conducted using SPSS. The findings revealed that while the surveyed students demonstrated a moderate level of financial knowledge, their financial behaviour and attitudes were at a high level. These results contributed to an overall high level of financial literacy. Consequently, the study highlights the need for schools, educators, and policymakers to implement targeted initiatives that not only improve financial knowledge but also maintain and enhance positive financial behaviours and attitudes.